Study on the estimate for seismic response of high-speed railway bridge-track system. (15th September 2022) - Yu, Jian; Zhou, Wangbao; Jiang, Lizhong
Highlights: Upper bound was proposed to estimate peak seismic response. Characteristic curve was proposed to estimate residual seismic response. The minimum record numbers for the two indexes were determined. Abstract: In recent years, China's High-speed railways (HSRs) construction has gradually extended to its western regions. Taking A HSR multi-span (5-span) simply-supported beam bridge-track system as the research object, this paper proposed two new indexes: upper bound used to estimate peak seismic response, and characteristic curve used to estimate residual seismic response. The minimum number of ground motions required for reasonably evaluating the two new indexes was determined. According to the findings, the maximum value of peak seismic response of the high-speed railway track-bridge system has significant discreteness, and the mean value of peak seismic response is significantly less than the maximum value. Therefore, it is not advisable to use the maximum value or the mean value of the peak seismic response as the estimate for seismic design. The upper bound for peak seismic response can be used as an effective estimate for seismic design, and the number of ground motion samples can be set to 20. The residual seismic deformation of bearings is the primary source of the residual seismic response of the HSR bridge-track system and that the post-earthquake maintenance of the bridge-track system should primarily focus on the replacement of bearings as well as the resetting of box girders and tracks. The characteristic curves for residual displacement of rail can effectively evaluate the earthquake-induced residual displacement of the HSR bridge-track system, and the number of ground motion samples can be set as 40.